The Effects of Socio-Demographical Factors and Perceived Seriousness Upon Motherly Skill of Managing Eating Disorder on Children with Avoidant Restrictive Food Intake Disorder (ARFID) - Yoyok Bekti Prasetyo (Journal of Global Pharma Technology, 2020)
Objective: Perceived seriousness is considered to mothers in making decisions for the sake of protective attempts upon children suffering from avoidant restrictive food intake disorder (ARFID). This study aimed to identifyy the predictor factors of motherly skill in managing eating disorder on children with ARFID. Method: A cross-sectional descriptive survey was held to 245 mothers taking care of children with ARFID. This research was conducted in 3 subdistricts and three community public health centres in Malang.  Data were collected by questionnaires of perceived seriousness and a managing eating disorder. Data were processed descriptively, using Pearson correlation and multiple linear regression (level of significant 0.05). Results: Factors in respect of motherly skill of managing eating disorder included the feeling of fear of children’s condition (p= 0.006), feeling of failure to contribute when children suffered from malnutrition (p= 0.010), serious condition (p= 0.017), and the whole-life changes (p= 0.002). The multiple-linear regression revealed that factors influenced motherly skill of managing eating disorder covered education (β = 1.089, p = 0.022), the number of children (β = -1.582, p = 0.025), and perceived seriousness (β = 0.097, p = 0.020). Conclusion: This current research had indicated that perceived seriousness was a significant factor to influencing mothers in making decisions for the sake of protection upon their children. Thus, we recommend that motherly belief is fostered in the event of health promotion.Keywords: Perceived seriousness, The skill of managing an eating disorder, ARFID.